Body Mass Index and Urinalysis Markers in the Seemingly Healthy Young Adults - Pradana, Krisnawan Andy; Kalanjati, Viskasari P; Tirthaningsih, Ni Wajan (Folia Medica Indonesiana, 2020)
Higher prevalence of albuminuria, glycosuria, and haematuria was reported in the obese people than control. We aimed to analyze the BMI and urinalysis markers among the university students aged 18-21 years old in the IIKBW, Kediri to study any correlations and differences between these variables, which to the best of our knowledge has yet widely reported in Indonesia. This study has ethics approval from Universitas Airlangga, Surabaya. The BMI was analyzed from the body weight and height of male (n=74) and female (n=76) students with no health problems recorded. The pH, nitrites, protein, erythrocytes, glucose in the urine were measured qualitatively with a dip-stick method, blinded, using the midstream urine sample collected in the morning. Data were analyzed using SPSS 17, with a level of significance of p<0.05. Abnormal pH (n=75), positive nitrites (n=24), haematuria (n=6), and proteinuria (n=149) were recorded. About 22% of students suffered from type I obesity, and 8.7% of type II. Males were significantly suffered from the obesity whilst females from the overweight (p<0.05). No significant correlations between the BMI and each urinalysis marker (BMI and nitrites p=0.936; BMI and protein p=1; BMI and pH p=0.835; BMI and blood, p=0.486; respectively); no one were found with glycosuria. No significant differences either on the BMI or the 5 urinalysis markers between male and female groups (p>0.05). Whilst no positive glycosuria samples were identified; 18.9% of males and 13.2% of females have positive nitrites, 100% of males and 98.7% of females have positive proteinuria, 2.7% of males and 7.9% of females have positive haematuria. There were 7.33% of males and 6% of females having an increased pH; whilst 20.66% of males and 16% of females having a decreased pH. Amongst the seemingly healthy university students, we found cases of urinalysis marker impairment, although no significant correlations on the BMI to the urinalysis markers that may be representing early detection for renal diseases were observed.